2020
DOI: 10.1186/s12902-020-00653-x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite biomarkers of type 2 diabetes mellitus and pre-diabetes: a systematic review and meta-analysis

Abstract: Background We aimed to explore metabolite biomarkers that could be used to identify pre-diabetes and type 2 diabetes mellitus (T2DM) using systematic review and meta-analysis. Methods Four databases, the Cochrane Library, EMBASE, PubMed and Scopus were selected. A random effect model and a fixed effect model were applied to the results of forest plot analyses to determine the standardized mean difference (SMD) and 95% confidence interval (95% CI) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 55 publications
10
46
0
Order By: Relevance
“…Metabolomics has already allowed the identification of metabolites that can serve as potential biomarkers for the diagnosis or treatment of T2DM [12]. The relationships between metabolites level and insulin resistance [13,14], prediabetes [15,16] and T2DM [4,17] have been evaluated in several studies using mass spectrometry (MS) coupled with gas (GC) or liquid (LC) chromatography.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics has already allowed the identification of metabolites that can serve as potential biomarkers for the diagnosis or treatment of T2DM [12]. The relationships between metabolites level and insulin resistance [13,14], prediabetes [15,16] and T2DM [4,17] have been evaluated in several studies using mass spectrometry (MS) coupled with gas (GC) or liquid (LC) chromatography.…”
Section: Introductionmentioning
confidence: 99%
“…All manuscripts were carefully studied, and biomarkers were identified and counted. The analysis of the results identified two approaches to novel prediabetic biomarkers: metabolomics [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], and microRNA studies [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. The results are shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Recent study conducted on 1,321 individuals with different risks for type 2 diabetes (i.e., from ADDITION-PRO cohort) did not provide genetic evidence for the causative role of BCAA in the development of insulin resistance, but suggested that insulin resistance itself can evoke higher plasma fasting BCAA concentrations (Mahendran et al 2017). Nevertheless, the elevation in plasma BCAA and BCKA levels predicted type 2 diabetes development in various study cohorts and preceded the disease by over 10 years (Long et al 2020;Arany and Neinast 2018;Wang et al 2011). Therefore, BCAA are valuable biomarkers for early detection and diagnosis of insulin resistance in non-diabetic obese patients and strong indicators of the later risk of type 2 diabetes (Zhao et al 2016) as well as potential biomarkers in the diagnosis of diabetes complications (Del Coco et al 2019).…”
Section: Bcaa As Markers Of Insulin Resistance and Type 2 Diabetesmentioning
confidence: 99%